Microbial ferric iron reductases - Schröder, Imke; Johnson, Eric; de Vries, Simon (FEMS microbiology reviews, 2003)
Almost all organisms require iron for enzymes involved in essential cellular reactions. Aerobic microbes living at neutral or alkaline pH encounter poor iron availability due to the insolubility of ferric iron. Assimilatory ferric reductases are essential components of the iron assimilatory pathway that generate the more soluble ferrous iron, which is then incorporated into cellular proteins. Dissimilatory ferric reductases are essential terminal reductases of the iron respiratory pathway in iron-reducing bacteria. While our understanding of dissimilatory ferric reductases is still limited, it is clear that these enzymes are distinct from the assimilatory-type ferric reductases. Research over the last 10 years has revealed that most bacterial assimilatory ferric reductases are flavin reductases, which can serve several physiological roles. This article reviews the physiological function and structure of assimilatory and dissimilatory ferric reductases present in the Bacteria, Archaea and Yeast. Ferric reductases do not form a single family, but appear to be distinct enzymes suggesting that several independent strategies for iron reduction may have evolved.